A fluid-structure interaction (FSI) and energy generation modelling for roof mounted renewable energy installations in buildings for extreme weather and typhoon resilience. (November 2020) - Pantua, Conrad Allan Jay; Calautit, John Kaiser; Wu, Yupeng
Abstract: The Philippines is visited by an average of 20 typhoons every year. Due to the damage to the infrastructure caused by the Typhoon, communities devastated by the typhoon are left without power. Solar panels can supply power to the affected community during power outages. However, these installations are also structurally vulnerable to extreme weather such as typhoons strength winds. A Fluid Structure Interaction (FSI) is implemented in a low-rise gabled building with roof mounted solar panels. This building was subjected to typhoon strength winds using Computational Fluid Dynamics (CFD) analysis. Building energy simulation (BES) was also performed in the same building to account for solar PV energy generation and energy consumption. The results from the FSI showed the areas of failure in the panels with regards to installation location. On the other hand, BES results showed that the highest power generation potential is based on the building orientation at 90° and roof pitch of 14°. It was suggested to install the panel system configuration to a 26° pitch roof to sustain occupancy loads. This framework which combines energy systems resilience and building energy performance can help the stakeholders to properly plan and design better disaster resilient infrastructures. Graphical abstract: Image 1 Highlights: An FSI and BES model was developed for buildings with roof mounted solar panels. The coupled FSI-BES model was implemented on 3 varying roof pitches. High solar panel failure rate was observed on a 14-degree roof pitch. The 26.5 pitch roof is the best case of energy generation and structural resiliency.